Novel Silane Crosslinked Chitosan Based Electrospun Nanofiber for Controlled Release of Benzocaine - Naz, Mehwish; Jabeen, Sehrish; Gull, Nafisa; Ghaffar, Abdul; Islam, Atif; Rizwan, Muhammad; Abdullah, Huda; Rasool, Atta; Khan, Shahzad; Khan, Rafi (Frontiers in Materials, 2022)
Electrospun nanofibers mats of chitosan (CTS)/polyvinyl alcohol (PVA)/halloysite nanoclay and CTS/PVA/halloysite nanoclay//3-glycidyoxypropyl trimethoxysilane loaded with drug was fabricated using the electrospinning method. Electrospun nanofiber samples were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and thermogravimetric analysis (TGA). FTIR confirmed the chemical and physical bonding among ingredients like CTS, PVA, nanoclay and crosslinker of nanofibers. SEM showed the development of uniform nanofibers. The average diameter of nanofiber was observed in the range of 50-200 nm. Antimicrobial activity was examined against E. coli and S. aurus bacteria. The results obtained indicated that all nanofiber samples showed the significant antimicrobial activity against the Gram positive as well as Gram negative bacteria. TGA results indicated that thermal stability of nanofibers increased with the addition of crosslinker. The drug release was studied in phosphate buffer saline (PBS) solution (pH 7.4) at 37 ˚C and drug was released from nanofibers in 2 h and 30 min. Hence, these prepared nanofibers could be used in medication where drug was required for long duration.